Democratic perception among youths and civic engagement in Cameroon: An analysis from the Civic Voluntarism Approach (African Journal of Law and Politics, 2023)
Apathy among youths when it comes to civic engagement is one the most pre-occupying issues in contemporary democracies. However, youths can still engage in civic action if the ideals of democracy are fulfilled. Amongst these ideals are: the principles of plurality, competiveness, free, fair and transparent elections, good governance, the rule of law, and the respect for fundamental human rights. Unfortunately, the effectiveness of these practices is still far-fetched in Cameroon. This is demonstrated by the timidity of youths in voting, attending political rallies, expressing interest in public affairs, attending protests or demonstrations and joining others in raising an issue of public concern. It is from this perspective that this article is aimed at addressing the question of the relationship between youth democratic perception and civic engagement. To realise this, data relied on the secondary quantitative data from the AFRO-BAROMETER Database of 2021 from a sample of 750. The data were descriptively analysed using tables and percentages. While basing this analysis from the Civic Voluntarism Theory, findings have revealed that civic engagement among Cameroonian youths depend on their views and opinions about democracy. Their negative views about democracy are accountable for their low rates of civic engagement. On this basis, recommendations are made to the government through the structures and agencies that have been charged with the responsibilities of promoting youth civic engagement, such as Elections Cameroon (ELECAM), the Ministry of Youth Affairs and Civic Education, and the National Civic Service Agency for Participation in Development, to put in place and reinforce the implementation of policies that foster youth civic engagement. Youths are also encouraged to develop the political consciousness of active civic engagement.